Multivalent dextran hybrids for efficient cytosolic delivery of biomolecular cargoes. (17th January 2021) - Becker, Bastian; Englert, Simon; Schneider, Hendrik; Yanakieva, Desislava; Hofmann, Sarah; Dombrowsky, Carolin; Macarrón Palacios, Arturo; Bitsch, Sebastian; Elter, Adrian; Meckel, Tobias; Kugler, Benedikt; Schirmacher, Anastasyia; et al.
Abstract : The development of novel biotherapeutics based on peptides and proteins is often limited to extracellular targets, because these molecules are not able to reach the cytosol. In recent years, several approaches were proposed to overcome this limitation. A plethora of cell‐penetrating peptides (CPPs) was developed for cytoplasmic delivery of cell‐impermeable cargo molecules. For many CPPs, multimerization or multicopy arrangement on a scaffold resulted in improved delivery but also higher cytotoxicity. Recently, we introduced dextran as multivalent, hydrophilic polysaccharide scaffold for multimerization of cell‐targeting cargoes. Here, we investigated covalent conjugation of a CPP to dextran in multiple copies and assessed the ability of resulted molecular hybrid to enter the cytoplasm of mammalian cells without largely compromising cell viability. As a CPP, we used a novel, low‐toxic cationic amphiphilic peptide L17E derived from M‐lycotoxin. Here, we show that cell‐penetrating properties of L17E are retained upon multivalent covalent linkage to dextran. Dextran‐L17E efficiently mediated cytoplasmic translocation of an attached functional peptide and a peptide nucleic acid (PNA). Moreover, a synthetic route was established to mask the lysine side chains of L17E with a photolabile protecting group thus opening avenues for light‐triggered activation of cellular uptake. Abstract : Joining Forces: Efficient intracellular delivery is still challenging. Herein, we report a drug delivery module based on L17E peptide multimerized on dextran scaffold. The construct showed efficient cytosolic/nuclear delivery of various cargoes of different size and function.